A CGE assessment of a university's effects on a regional economy - supply-side versus demand-side effects - James Giesecke; John Madden (European Regional Science Association (ERSA), 2005)
In recent years many universities have commissioned studies of the effect of their institution on the local economy. Typically these impact studies have concentrated on the demand-side stimuli to the regional economy that the university generates. Normally, the studies are undertaken with comparative-static input-output models. The present study employs a dynamic multiregional computable general equilibrium model to investigate supply-side as well as demand-side effects. There are a range of supply-side effects that have been investigated in the spatial econometrics literature. The supply-side impacts of the university that we examine in particular are a rise in the average skill level of the local workforce, and successful R&D outcomes. CGE modelling allows simulation of the associated productivity effects, while the dynamic features of the model allow for consequent effects on the region's population and capital stock growth rates to be taken into account.
Keywords: 330